School Infrastructure Inequality and the Reproduction of Educational Disadvantage: A Bourdieusian Analysis of Cultural Capital Formation in Marginalized Regions - Muhamad Rayhan Al-Arif; Choirunnajih Hadanil Alqo; Muhamad Aufa Ulinnuha; M. Rikza Chamami; Muhammad Imran Musthofa (Journal of Islamic Education Thought and Development, 2026)
Educational inequality remains a persistent challenge in disadvantaged regions, where disparities in school infrastructure continue to shape unequal learning opportunities and educational outcomes. This study investigates how infrastructural inequalities contribute to the reproduction of educational disadvantage among senior high school students in Wonogiri, Indonesia, through the lens of Pierre Bourdieu’s Social Reproduction Theory. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving students, teachers, school leaders, and local education stakeholders. Data were analyzed using the Miles and Huberman interactive framework to identify patterns linking material conditions to educational experiences and outcomes. The findings reveal that unequal access to educational infrastructure—including laboratories, libraries, digital technologies, and internet connectivity—creates significant disparities in students’ opportunities to acquire cultural capital. Students in rural and geographically marginalized schools experience limited exposure to academic practices, digital competencies, and skill-development opportunities compared with their counterparts in better-resourced schools. These disparities constrain educational achievement and reduce students’ capacity to compete in higher education and labor markets. The study demonstrates that infrastructural inequality functions not merely as a resource deficit but as a structural mechanism through which educational disadvantage is reproduced across generations. This research extends Bourdieu’s framework by highlighting the mediating role of school infrastructure in the conversion of economic capital into cultural capital within disadvantaged educational settings. The findings suggest that equitable infrastructure investment is essential for disrupting cycles of educational inequality and promoting inclusive human capital development. Consequently, policies aimed at reducing regional disparities must prioritize the redistribution of educational resources to ensure more equitable learning opportunities and social mobility.